2016
DOI: 10.1097/coc.0000000000000066
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predictive of Improved Outcomes With Multimodality Local Therapy After Palliative Chemotherapy for Stage IV Esophageal Cancer

Abstract: Aggressive local therapy with radiation and potentially surgery after initial palliative chemotherapy can improve prognosis for a select group of patients with stage IVB esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 25 publications
4
36
0
Order By: Relevance
“…Given the limited of studies with small sample sizes investigating the effect of local treatment in metastatic EC10111213. In this study, we explored the prognostic value of local treatment modalities including CDS and RT in metastatic EC based on 9,125 metastatic EC patients in the SEER database and our results found that surgery plus RT could significantly improve survival in metastatic EC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the limited of studies with small sample sizes investigating the effect of local treatment in metastatic EC10111213. In this study, we explored the prognostic value of local treatment modalities including CDS and RT in metastatic EC based on 9,125 metastatic EC patients in the SEER database and our results found that surgery plus RT could significantly improve survival in metastatic EC.…”
Section: Discussionmentioning
confidence: 99%
“…RT is not a first-line treatment for metastatic EC, but RT may improve the patients’ symptoms of obstruction9. Studies with small sample sizes have shown that local treatments including surgery could prolong survival in metastatic EC10111213. Studies have shown that surgery and/or radiotherapy can improve survival in patients with stage IV malignant tumors1415.…”
mentioning
confidence: 99%
“…The worldwide standard of total 50.4 Gy irradiation for esophageal cancer without distant metastasis was used, and treatment was given with palliative intent, so the radiation dose of 50 Gy was thought to be reasonably safe. Previous studies have investigated age, distant metastasis, baseline white blood cell count, change in standardized uptake value in PET after chemotherapy, lack of anorexia/cachexia, and lack of widely disseminated disease as predictors of OS (26,27). We found that a small group of eight patients who underwent surgery after CCRT had more favorable OS than that of patients who did not have surgery.…”
Section: Discussionmentioning
confidence: 59%
“…These findings are closely mirrored by Gandy et al [23], with a 60% 5-year OS after liver resection in a cohort of 48 patients, 2 of which were affected by liver OEC. In a retrospective study including 96 patients, Wang et al [15] reported that a small subset of 14 patients who were treated with a multimodal approach including liver resection showed a more favorable prognosis compared to patients who did not undergo surgery. Similarly, Carmona-Bayonas et al [24] reported that 92 patients who underwent surgery for EC metastasis had a higher survival rate than patients who did not undergo metastasectomy (30% versus 8%).…”
Section: Surgerymentioning
confidence: 99%
“…Alternative therapeutic options generally include CHT and loco-regional therapies. More recently, small trials have reported that patients with low hepatic tumor burden have a favorable prognosis after CHT followed by liver resection [9,[14][15][16]. Indeed, the prognosis of patients with non-surgically treated liver OEC still remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%